Earth Sciences and Archaeology
XXI, 513 p.
Keywords: Earth Sciences and Archaeology brings together contributions from an experienced group of archaeologists and geologists whose common objective is to present thorough and current reviews of the diverse ways in which methods from the earth sciences can contribute to archaeological research. Many areas of research are addressed here, including artifact analysis and sourcing, landscape reconstruction and site formation analysis, soil micromorphology and geophysical exploration of buried sites. Archaeology has benefited from geological methods in many ways in recent decades. However, in the past ten to twenty years, this informal collaboration between geologists and archaeologists has grown into a formal integration of earth science and archaeology on a significant scale. This book allows the contributors to assess where we are in terms of interdisciplinary research, which approaches work best in specific situations, and where this collaborative approach should progress to in the future.